Investigation of Strongyle Prevalence and Associated Risk Factors in Horses in and around Alage District, Ethiopia - Mulugeta Tesfaye Alemayehu; Belete Kuraz Abebe; Sharew Mekonnen Haile (Journal of Parasitology Research)
Background. Horses are used for a variety of purposes in Ethiopia. However, their service is hampered by a variety of health issues. Strongylosis is a parasitic infestation of the gastrointestinal tract that has a significant impact on the working ability, reproductive performance, well-being, and welfare of horses. The existence of Strongylosis in the study area is reported from clinical cases; however, its prevalence has not been well studied. Objective. The current study was carried out from January 2019 to July 2019, to determine the prevalence and associated risk factors of Strongyle in horses in and around Alage district. Methods. A cross-sectional study design was used, and 384 horses were sampled from three peasant associations inseparably. The floatation technique was used in laboratory analysis. Result. Strongylosis was discovered in 67.19 percent of the cases. In Naka, Dilbato, and Koricho peasant associations, the infestation magnitudes were 64.1%, 68%, and 69.5%, respectively. The increased level of animal-related prevalence was observed in male (68.1 percent), young (84.4 percent), and poor body condition (90 percent) horses. Age and body condition scores were statistically significant associations with the disease under study at p≤0.000. While sex and peasant associations did not predict the problem significantly (p≤0.05), young horses and horses in poor and medium body conditions are 4.66 (CI: 2.22–9.76), 9.63 (CI: 3.77–24.63), and 1.93 (1.03–3.60) times more likely to be infected with Strongylosis, respectively. Conclusions. The occurrence of Strongylosis is determined independently by age and BCS. Strongyle infestations are common in horses in the study area, posing a significant barrier to horse production and well-being. As a result, appropriate disease prevention and control measures should be implemented.